Agronomic and Economic Interactions between Sidedressed Nitrogen and Potassium Fertilizations on ‘Atlantic’ Potato - Yagi, Renato; Xavier de Nazareno, Nilceu Ricetti; Soratto, Rogério Peres [UNESP] (FapUNIFESP (SciELO), 2020)
Nitrogen (N) and potassium (K) in potato crop planting synergistically increase tuber yield, but there are no studies on this interaction in sidedressing. In two experiments with ‘Atlantic’ potato combinations of four N rates (0, 50, 100, and 150 kg ha-1) with four K2O rates (0, 100, 200, and 300 kg ha-1) were applied in sidedressing in a 4×4 factorial scheme with three replications in a completely randomized design. Adjacent commercial fields were sampled to economic comparisons with experimental results. Significant interaction between N and K sidedressing rates with tuber yields increase also was confirmed and classified as Liebig-synergism. Compared to the isolated N and K applications in sidedressing, joint N and K fertilizations, respectively, increases by 11% and 48% marketable tuber yields in the summer-fall experiment, and 12% and 7% in the spring experiment. Joint N and K applications as sidedressing was more profitable than planting fertilization, mainly at higher N and K rates. The response of specific gravity of ‘Atlantic’ potato tubers to the N and K sidedressing rates was mediated by interactions between edaphoclimatic conditions and inputs of N and K. The combined application of N and K sidedressing rates increased specific gravity in the summer-fall experiment, but had a negative effect in the spring experiment. Therefore, our results provide strong evidence that the fertilization management for potato crop in Brazil can be modified by applying higher amounts of N and K in sidedressing to match nutritional needs of the crop.
Keywords: mineral nutrition; Solanum tuberosum; synergistic effect